(untitled) (Semiárida, 2020)
This paper reporta a wofi on growth straina of the Rhizobium and Bradyrllizobium, in a batch system, in order to obtain microorganisms suspension of a very high can concentration. In the process of designing the culture media the influence of the aeration and the nutrient concentration is considered. The experiments were carried out in a er1enmeyers flask on rotatory shaker and in laboratory fermentors. The evolution of cen growth was determined according to measures of optical density, viable cen count and dry weight. Using a selected balanced media and strains such as Rhizobium meliloti B 36, B 399, Rhizobium trifolii A 113, Rhizobium loti LL 22, Rhizobium leguminosarum O 70 and Bradyrhizobium japonicum E 109, E 110 and E 45, it was possible to obtain microorganisms concentrations of 6 x 1010 to 1 x 1011 viable cell ml in 48 and 96 hour processes, corresponding to dry weight concentrations higher than 10 gIl. The osmotical presure in the selected medium was in the order of 300 miliosmoles. The modifications introduced in the culture media to achieve high microorganisms concentration did not alter the nitrogen fixation pacíty of the strains.